Soluble and Solid Supported Keggin Heteropolyacids as Catalysts in Reactions for Biodiesel Production: Challenges and Recent Advances - J. Da Silva, Marcio; A. Liberto, Natalia (Current Organic Chemistry, 2016)
Transforming renewable raw materials into biofuels has attracted growing attention due to economic and environmental reasons. The inevitable depletion of fossil fuels, and the increasing generation of greenhouse gas have motivated the development of environmentally friendly processes for biodiesel production. The conversion of acid non-edible vegetal oils using recyclable catalysts has been the goal pursued by research groups around the world. Heteropolyacids are attractive alternative because these are catalysts with acidic properties, which may be easily tunable by structural changes and can be supported on solid with high surface area. Heteropolyacids are oxygen cluster coordinates to addenda atom (i.e. W, Mo, V), which are coordinated to only central atom (i.e. P, Si, As). Biorefinery processes have intensively used this versatile class of catalysts to convert biomass derivative-platform molecules into chemicals and biofuels. Currently, solid supported heteropolyacids have been the catalysts used in various routes to produce biodiesel from vegetable oils and other lipidic feedstock. The combination of renewable and affordable raw materials with efficient solid catalysts (i.e. heteropolyacids) is doubtlessly an industrially strategic route for biodiesel production, and has been widely studied. In this review, the latest research and innovation towards developing processes for biodiesel production based on heteropolyacids will be highlighted. Particular attention was paid to the processes performed in liquid phase under heterogeneous catalysis conditions. Heterogeneous processes have been performed on solid supported heteropolyacids; carbon fibers, silica, zirconia, nanotubes, and niobium are examples of support discussed in this review. In this review, effort was made to describe the advances achieved in the heteropolyacid-catalyzed routes in converting triglycerides and fatty acids into biodiesel. The main synthesis methods and characterization of solid supported heteropolyacids were also addressed.
Keywords: solid catalysts